Determinants of Sexual Activity in Four Birth Cohorts of Swedish 70‐year‐olds Examined 1971–2001. (1st February 2014) - Beckman, Nils; Waern, Margda; Östling, Svante; Sundh, Valter; Skoog, Ingmar
Abstract: Introduction: Knowledge about determinants of sexual activity in older adults in the general population is limited. Human senescence has been delayed by a decade, and people are reaching old age in better health. Aim: The aim of this study was to investigate determinants of sexual activity in four birth cohorts of non‐demented 70‐year‐olds examined in 1971–1977 and 1992–2001. Main Outcome Measure: The main outcome measure was sexual activity (defined as intercourse) during the past year. Methods: The study is based on cross‐sectional data from four population samples of 70‐year‐olds from Gothenburg, Sweden (N = 1, 407) systematically sampled from the Swedish population register. Results: In the time periods 1971–1972 and 2000–2001, sexual activity among men increased from 47% to 66%, and in women from 12% to 34%. Sexual activity was related to positive attitude toward sexuality, sexual debut before age 20, having a very happy relationship, having a physically and mentally healthy partner, self‐reported good global health, interviewer‐rated good mental health, being married/cohabiting, satisfaction with sleep, and drinking alcohol more than three times a week. Having an older partner, diabetes mellitus, coronary heart disease, higher physical health‐sum score, and depression were related to less sexual activity. Interaction effects for birth cohort, with stronger positive associations in 1971–1972, were found for positive attitude toward sexuality, strong desire at age 20–30, premarital sexuality, having a younger partner, self‐reported good global health, interviewer‐rated good global mental health, overweight, and satisfaction with sleep. Having an older partner and depression showed stronger negative associations in the 1970s. Physical health‐sum score showed a stronger negative association in 1992–2001. Conclusions: We found that determinants of sexual activity in older people are numerous and varied, and change over time. It is thus important that health professionals and others take a holistic approach when dealing with sexual problems in older adults. Sexual aging should be part of health care and medical education. Clinicians should be trained to ask older patients about sexual concerns.